2010
DOI: 10.1038/nm.2111
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 replication and immune dynamics are affected by raltegravir intensification of HAART-suppressed subjects

Abstract: Highly active antiretroviral therapy (HAART) results in potent and durable suppression of HIV-1 viremia. However, HIV-1 replication resumes if therapy is interrupted. Although it is generally believed that active replication has been halted in individuals on HAART, immune activation and inflammation continue at abnormal levels, suggesting continued, low-level viral replication. To assess whether active replication might be driving immune activation in HAART, we examined the impact of treatment intensification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
353
5
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 482 publications
(388 citation statements)
references
References 32 publications
25
353
5
5
Order By: Relevance
“…This is at variance with a recent report by Lorenzo-Redondo et al [25] and a few earlier reports [23,24], but agrees with several other earlier studies [5,13,[17][18][19][20][21]. Lorenzo-Redondo et al [25] compared genetic diversity in samples HIV-1 RNA in plasma at start of therapy with HIV-1 DNA sequences obtained from blood and tissues at baseline, three and six months after the start of treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is at variance with a recent report by Lorenzo-Redondo et al [25] and a few earlier reports [23,24], but agrees with several other earlier studies [5,13,[17][18][19][20][21]. Lorenzo-Redondo et al [25] compared genetic diversity in samples HIV-1 RNA in plasma at start of therapy with HIV-1 DNA sequences obtained from blood and tissues at baseline, three and six months after the start of treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Most studies indicate that the HIV-1 reservoir is maintained by the physiological homeostasis of CD4 memory that in part involves occasional expansions and contractions of individual CD4 cell clones [5,12,22]. However, some studies have suggested that persistent virus replication may be an important contributor to the maintenance of the HIV-1 reservoir [23,24]. In particular, Lorenzo-Redondo et al [25] recently reported evidence of rapid HIV-1 evolution in lymphoid tissue reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…(30,31), suggesting that cART is effective in preventing viral replication in these anatomical sites. In contrast, increased numbers of 2-long terminal repeat circles in peripheral blood mononuclear cells and decreased amounts of unspliced HIV-1 RNA in CD4 + T cells isolated from the terminal ileum have been reported during raltegravir intensification, supporting the concept that some viral replication can occur despite suppressive cART (32,33). Thus, the role of on-going replenishment via cycles of replication as a cause of persistence is not fully understood.…”
Section: Significancementioning
confidence: 99%
“…This hypothesis builds first on the link between the size of the reservoir and the degree of inflammation, arguing that persistent virus production during ART could sustain immune activation (IA) and downstream pathological consequences (23, 24), and second on drug distribution studies in animal models of AIDS in which drug concentrations in tissues have been shown to differ from PB levels (25,26). Supporting this argument is the observation that some (but not all) intensification schemes with the integrase inhibitor raltegravir demonstrated a transient increase in 2LTR circles and decreases in IA, suggesting ongoing replication in a tissue site that is not reflected by measures in PB (27,28).We prospectively treated 12 subjects with ARVs and performed multiple samplings of LN, ileum and rectum, and PB after initiating ART to determine intracellular (IC) concentrations of the ARVs in these tissues and to assess the impact of treatment on virus production, measured by reduced numbers of productively infected HIV-1-RNA + cells and HIV-1 RNA in virions associated with the FDCn. Ten of the subjects were naïve to ART, and two subjects had been previously treated but had been off therapy for >1 y.…”
mentioning
confidence: 99%